The Influence of School Climate on Teacher Innovation in Early Childhood Education Mediated by Teacher Self-Efficacy - Naili Sa'ida; Nina Veronica; Tri Kurniawati (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
The research aims to analyze the influence of school climate on early childhood education teachers' innovation with teachers' self-efficacy as a mediating variable. This research uses a quantitative approach with an explanatory research design. The population of early childhood education (ECE) teachers in East Java Province, with a sample of 200 teachers selected using the multistage cluster random sampling technique. Data were collected thru a questionnaire using a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM). The research results indicate that the research model fits well with the empirical data (CMIN/DF = 1.284; RMSEA = 0.038; GFI = 0.934; AGFI = 0.907; CFI = 0.976; TLI = 0.968). The school climate has a positive and significant effect on teachers' self-efficacy (β = 0.620; p < 0.001), teachers' self-efficacy has a positive and significant effect on teachers' innovation (β = 0.540; p < 0.001), and the school climate has a positive and significant effect on teachers' innovation (β = 0.280; p = 0.001). Additionally, teachers' self-efficacy partially mediates the effect of school climate on teachers' innovation with an indirect effect value of 0.335 (p = 0.003). These findings indicate that a conducive school climate can enhance teachers' innovation both directly and by strengthening teachers' self-efficacy.